2015
DOI: 10.1002/jcb.25360
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Autophagy Increases 2-Methoxyestradiol-Induced Cytotoxicity in SW1353 Chondrosarcoma Cells

Abstract: Chondrosarcoma is a cartilage tumor and is the second most common malignant bone cancer. Unlike many tumors, chondrosarcomas are resistant to conventional chemotherapy and radiotherapy. Autophagy is a homeostatic mechanism through which cellular proteins and organelles are subjected to lysosomal degradation and recycling. Autophagy could play a dual role in cancer by facilitating either cell death or cell survival. To determine whether autophagy plays a role in cell death in chondrosarcoma, we have studied the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Moreover, it has been suggested the molecular crosstalk between 2-ME-induced apoptosis and autophagy is associated with its impact on microtubule integrity in cervical adenocarcinoma cells (62). On the other hand, the inhibition of autophagy increased the anticancer potential of 2-ME in chondrosarcoma cells (63). Thus, autophagy could play a dual role in cancer by facilitating either cell death or cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been suggested the molecular crosstalk between 2-ME-induced apoptosis and autophagy is associated with its impact on microtubule integrity in cervical adenocarcinoma cells (62). On the other hand, the inhibition of autophagy increased the anticancer potential of 2-ME in chondrosarcoma cells (63). Thus, autophagy could play a dual role in cancer by facilitating either cell death or cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the regulation of Atg3 on the conversion of LC3-I to LC3-II was also identified in chondrosarcoma cells. siRNAs against Atg3 blocked 2methoxyestradiol-induced autophagosome formation in cultured chondrosarcoma cells (39). At present, the regulatory mechanism involved in HDAC1-caused Atg3 downregulation in Schwann cells has still not been reported, and we speculate that HDAC1 might affect Atg3 in 2 different manners: direct regulation of Atg3 protein acetylation and indirect regulation of histone acetylation located in Atg3 promoter, which needs further exploration.…”
Section: Discussionmentioning
confidence: 81%
“…As a putative adaptive catabolic process, autophagy plays an important role in many human cancers, and the inhibition of autophagy in these conditions can lead to increased chondrosarcoma cell death. Reumann et al reported that the inhibition of autophagy increased 2-Methoxyestradiol-induced cytotoxicity in SW1353 chondrosarcoma cells [41], and Xing et al found that the knockdown of HOTAIR inhibited autophagy, which favored chondrosarcoma cell death [42]. Moreover, Gao et al observed that autophagy protected chondrosarcoma cells from siBMPR2-induced apoptotic cell death [43].…”
Section: Discussionmentioning
confidence: 99%